Ammonia Formation in Diethylenetriamine-Methyldiethanolamine (DETA-MDEA) System in the Presence of O2 During Amine-based Capture of CO2 from Combustion Flue Gases. (July 2017) - Maneelam, Kamonchanok; Saiwan, Chintana; Idem, Raphael; Supap, Teeradet
Abstract: Ammonia (NH3 ) is a major volatile degradation product formed from oxidative degradation of diethylenetriamine (DETA), methyldiethanolamine (MDEA), and their blend. Three molars DETA and MDEA were used in their single amine systems while mixture of the two amines using 1.5 M each was also tested. The reaction was operated at 0.65 CO2 loading, 6% mole O2, and 393 K. The results indicated that DETA generated NH3 from the oxidative degradation in liquid and gas phases the most, followed by 1.5 M DETA/1.5 M MDEA blend and single MDEA.